Analisis Beberapa Faktor Penyebab Kemiskinan Petani Di Kecamatan Kupang Timur – Kabupaten Kupang - Melgiana S. Medah (Politeknik Pertanian Negeri Kupang, 2013)
Causative factors of the East-Kupang farmers’ poverty was quite various, among other, the low availability of land for farmers, narrow farming land, semi-traditional technology, and low productivity of farming land. Those led to low income triggering poverty of the farmers. The purpose of this study was: 1) to describe the characteristics of poor farmers in the East Kupang subdistrict; 2) to identify the Contributing Factors to Farmers' Poverty in the East Kupang subdistrict. This applied quantitative descriptive method. Sampling technique applied the simple random sampling with a sample size of 160 farmers in the East Kupang subdistrict. Meanwhile, this employed the Path Analysis for data analysis. The results showed the characteristics of the poor farmers in the East Kupang subdistrict viewed from the low education of 62.50 percen and low working-capital of 66 percen. Utilization of semi-traditional agricultural technologies was 65.63 percen; 91 percent of farmers did not make a use of credit access; outpouring of working time in the agricultural sector ranged between 5-8 hours/ day; 73.75 percen and 43.75 percen of farmers quite often held five parties in 6 (six) months. Contributing factors to the farmers' poverty in the East Kupang subdistrict were the geographic and environmental factors 82.5 percen, followed by an economic factors 5.1 percen and social and cultural factors 3.2 percen and income contributed to their poverty by 34.4 percen. Key words: poverty, personal and physical factors, economic factor, social and cultural factors, geographical and environmental factors